2018
DOI: 10.3390/molecules23102634
|View full text |Cite
|
Sign up to set email alerts
|

The Positional Isomeric Effect on the Structural Diversity of Cd(II) Coordination Polymers, Using Flexible Positional Isomeric Ligands Containing Pyridyl, Triazole, and Carboxylate Fragments

Abstract: To systematically investigate the influence of the positional isomeric effect on the structures of polymer complexes, we prepared two new polymers containing the two positional isomers ethyl 5-methyl-1-(pyridin-3-yl)-1H-1,2,3-triazole-3-carboxylate (L1) and ethyl-5-methyl-1-(pyridin-3-yl)-1H-1,2,3-triazole-4-carboxylate (L2), as well as Cd(II) ions. The structures of the metal–organic frameworks were determined by a single crystal XRD analysis. The compound [Cd(L1)2·4H2O] (1), is a hydrogen bond-induced coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Neutral mononuclear complexes with general formula [M(L) 2 ·(H 2 O) 2 ] were obtained according to the procedure previously reported (see Figure 1 ) [ 38 ]. Slow diffusion of the reactants in immiscible liquids ( n -BuOH/H 2 O) resulted in the formation at the interphase of single crystals suitable for XRD analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutral mononuclear complexes with general formula [M(L) 2 ·(H 2 O) 2 ] were obtained according to the procedure previously reported (see Figure 1 ) [ 38 ]. Slow diffusion of the reactants in immiscible liquids ( n -BuOH/H 2 O) resulted in the formation at the interphase of single crystals suitable for XRD analysis.…”
Section: Resultsmentioning
confidence: 99%
“…grade and used without further purification (Sigma-Aldrich, St. Louis, MO, United States). The syntheses of the ester precursor and the sodium salt of the carboxylate ligands were carried according to the procedure previously described by Brito et al and reported elsewhere [ 38 ]. On the other hand, the 1-bis-ethyl 1-(3,4-dimethylphenyl)-5-methyl-1 H -1,2,3-triazol-4-carboxylate diacquo Zn(II) or Cd(II) complexes (compounds 1 and 2, respectively), were obtained by double layer solution diffusion in crystallization at room temperature using a test tube (15 cm length by 1.5 cm diameter) between 50 mg (0.197 mmol, 2 eq.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuation of our previous investigation on coordination polymers 13,14,[24][25][26][27] , in this work, we present the synthesis, structural characterization and energetic properties of the new coordination polymer strontium benzilate. Hirshfeld surface analysis 28 was used for visually analyzing intermolecular interactions in the crystal structure.…”
Section: Introductionmentioning
confidence: 93%
“…The fine selection of positionally isomeric organic ligands, and their role in the structure of the CP, is a relevant aspect to study since it can also affect their physical properties. For instance, the isomeric effect [ 28 , 29 , 30 ] over coordination metal complexes can generate the difference between molecular or extended solids [ 25 , 30 , 31 ] and can affect the luminescent and thermal properties. Specifically, the luminescent properties could be modified on demand by appropriately selecting these building blocks.…”
Section: Introductionmentioning
confidence: 99%